2022
DOI: 10.1002/admi.202201406
|View full text |Cite
|
Sign up to set email alerts
|

Thru‐Hole Epitaxy: A Highway for Controllable and Transferable Epitaxial Growth

Abstract: Controllable growth and facile transferability of a crystalline film with desired characteristics, acquired by tuning composition and crystallographic orientation, become highly demanded for advanced flexible devices. Here the desired crystallographic orientations and facile transferability of a crystalline film can be achieved by “thru‐hole epitaxy” in a straightforward and undemanding manner with no limitation on the layer number and polarity of a 2D space layer and the surface characteristics. The crystallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…At the onset of growth of GaAs on graphene/GaAs, there is an interplay between different nucleation mechanisms including remote epitaxy, pinhole-seeded epitaxy, nucleation at impurities, graphene defects or carbides, and possibly Van der Waals epitaxy. Remote and pinhole seeded epitaxy provide an epitaxial alignment with the substrate and it is provenly complicated to differentiate both experimentally 2,11 . On the other hand, XPS reproducibly showed no Ni or other transfer-related contaminants, nor carbides in the C 1s peak after annealing in UHV or H2.…”
Section: Characterizationmentioning
confidence: 99%
“…At the onset of growth of GaAs on graphene/GaAs, there is an interplay between different nucleation mechanisms including remote epitaxy, pinhole-seeded epitaxy, nucleation at impurities, graphene defects or carbides, and possibly Van der Waals epitaxy. Remote and pinhole seeded epitaxy provide an epitaxial alignment with the substrate and it is provenly complicated to differentiate both experimentally 2,11 . On the other hand, XPS reproducibly showed no Ni or other transfer-related contaminants, nor carbides in the C 1s peak after annealing in UHV or H2.…”
Section: Characterizationmentioning
confidence: 99%
“…[ 12 ] We indeed showed that this can be possible without those stringent conditions required for remote epitaxy by demonstrating not only the growth of crystallographically aligned GaN domains over a 2D material, such as h ‐BN, but also the facile detachment of those grown and merged GaN domains. [ 13 ] This epitaxial approach was named thru‐hole epitaxy. Note that the term “thru‐hole” is used to refer to a hole connected all the way from the top‐most 2D material to the substrate resulting in the establishment of the epitaxial connectedness between the material grown and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike remote epitaxy, which stringently requires a defect‐free graphene monolayer, we observed that thru‐hole epitaxy can be successfully carried out with tens of nanometers thick (multiply‐stacked) h ‐BN layers or even thicker SiO2$\left(\text{SiO}\right)_{2}$ as long as thru‐holes are maintained. [ 13 ] Here, a “stack” represents a transfer unit consisting of multiple layers of h ‐BNs grown together at the same time. Crystallographically‐aligned GaN domains were successfully grown over multiply‐stacked h ‐BN transferred onto the sapphire substrate and easily detached with a thermal release tape.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations